PEMBUATAN WEBSITE SEBAGAI MEDIA PEMASARAN PT. KARYA PANCANG JAYA (Jurnal AbdiMas Nusa Mandiri, 2025)
The rapid advancement of digital technology has transformed the way companies promote their products and services, shifting from conventional methods to internet-based marketing strategies. The internet serves as an effective marketing medium to expand customer reach and strengthen business competitiveness through fast and broad information dissemination. PT. Karya Pancang Jaya is a construction service company specializing in pile foundation installation for various types of buildings. However, the company’s marketing activities have relied primarily on conventional approaches such as brochures, exhibitions, and customer referrals. To address this limitation, a community service program was carried out by lecturers from Universitas Atma Jaya Makassar through the development of a company website as a digital marketing medium. The program consisted of four stages—observation, preparation, implementation, and evaluation—conducted over a period of three months, from December 10, 2024, to February 12, 2025. The results indicate that the developed website has been successfully hosted and launched, featuring comprehensive information about the company profile, services, and completed projects. This website is expected to strengthen PT. Karya Pancang Jaya’s digital presence and improve its marketing effectiveness.